Asupan Zat Gizi Dan Berat Badan Ibu Hamil Kekurangan Energi Kronik Selama Program Konseling Gizi Dan Pemberian PMT - Melinda Melinda; Nadimin Nadimin; Sukmawati Sukmawati; Agustian Ipa (Media Kesehatan Politeknik Makassar, 2023)
ABSTRACT Chronic Energy Deficiency (CED) is a nutritional problem for pregnant women that needs more attention. Riskesdas 2018 data shows the prevalence of CED pregnant women aged 15-49 years in Indonesia is 17.3%, in South Sulawesi province by 16.87%, and in Makassar City by 13.02%. The purpose of this study was to determine the effect of counseling on nutritional intake and body weight of CED pregnant women in the working area of the Tamalanrea Jaya Health Center in Makassar City. The research design used was pre-experimental with a one group pretest-postest design without a control group. The sample in this study was CED pregnant women who were selected by purposive sampling as many as 10 people with criteria for pregnant women who had an upper arm circumference of <23.5 cm. Nutrient intake data was obtained by the 24-hour recall method and weight data was measured using a digital weight scale. Data analysis in this study used the Wilcoxon test. The results showed that the average nutritional intake of CED pregnant women both energy, protein, fat, and carbohydrates was low (< 60% RDA of pregnant women). The results of the analysis showed no effect of nutritional counseling on the nutritional intake of CED pregnant women, ranging from energy (p = 0.878), protein (p = 0.203), fat (p = 0.575), and carbohydrates (p = 0.508). The provision of counseling has an influence on the weight of pregnant women between before and after nutritional counseling (p = 0.012). The conclusion of this study is that nutritional counseling has not been able to increase nutrient intake until nutritional needs are met, but it can increase the weight of CED pregnant women.